Cablegram (translation)
012a-0097-001 TRANSLATION OF CABLEGRAM FROM EXECUTIVE COMMISSION OF THE SPANISH U.G.T. (UNION GENERAL DE TRABAJADORES). CITRINE, BRITISH TRADES UNIONS, SMITH SQUARE, LONDON. DIRECT BAREFACED PARTICIPATION (OF) ITALY (AND) GERMANY, WITH USE OF MEN AND MATERIAL, PARTICULARLY AEROPLANES, USED IN HUNDREDS IN RECENT MILITARY OPERATIONS AND CRUEL ATTACKS AGAINST OPEN TOWNS. IN FACE OF INTENSIFICATION AND OBDURATENESS OF THE FIGHT IN OUR COUNTRY, WHICH SEES ITSELF PREVENTED FROM ACQUIRING AEROPLANES TO BE ABLE TO OPPOSE THE GERMAN AND ITALIAN AIRCRAFT, WE ASK FOR DECISIVE ACTIONS (IN THE) FIGHT AGAINST ARMS EMBARGO. SPANISH REPUBLICAN GOVERNMENT HOPING ENERGETIC ATTITUDE (OF) WORKERS' ORGANISATION IN FAVOUR OF FREEDOM (OF) COMMERCE. SOLIDARITY (OF) SPANISH PROLETARIAT IS DEFENDING PEACE (OF) EUROPE (AND) PRINCIPLES OF LIBERTY AND DEMOCRATIC FRONT. FORMATIONS REGULAR ITALIAN (AND) GERMAN ARMY (WITH) ENORMOUS SUPERIORITY (OF) ARMAMENTS ARE MASSACRING HEROIC DEFENDERS (OF) INDEPENDENCE (OF) SPAIN ADVANCING ON PYRENEES, PART OF FASCISTS' WAR ACCORDING TO OWN DECLARATION. AC/427.14. 292/946/12a/97(i)